Gridlets: Reusing Spreadsheet Grids - Joharizadeh, Nima; Sarkar, Advait; Williams, Jack; Gordon, Andy (38th Annual ACM Conference Extended Abstracts on Human Factors in Computing Systems (CHI '20 Extended Abstracts), 2020)
Spreadsheets allow end users to blend calculations with arbitrary layout and formatting. However, when it comes to reusing groups of formulae along with layout and format-ting, spreadsheets provide only limited support. Most users rely on copy and paste, which is easy to learn and use, but maintaining several copies can be tedious and error-prone. We present the concept of Gridlets, an abstraction over calculation and presentation applicable in common use case scenarios. Using the Cognitive Dimensions of Notations framework, we compare Gridlets to copy/paste and sheet-defined functions. We find that Gridlets are consistent with the spreadsheet paradigm, enable users to take advantage of secondary notation, and make common edit operations less viscous and less error-prone.